Fabrication of tailorable pH responsive cationic amphiphilic microgels on a microfluidic device for drug release. Issue 1 (15th October 2017) - Lu, Bingyuan; Tarn, Mark D.; Pamme, Nicole; Georgiou, Theoni K.
ABSTRACT: Cationic, amphiphilic microgels of differing compositions based on hydrophilic, pH, and thermoresponsive 2‐(dimethylamino)ethyl methacrylate (DMAEMA) and hydrophobic, nonionic n ‐butyl acrylate (BuA) are synthesized using a lab‐on‐a‐chip device. Hydrophobic oil‐in‐water (o/w) droplets are generated via a microfluidic platform, with the dispersed (droplet) phase containing the DMAEMA and BuA, alongside the hydrophobic cross‐linker, ethylene glycol dimethacrylate, and a free radical initiator in an organic solvent. Finally, the hydrophobic droplets are photopolymerized via a UV light source as they traverse the microfluidic channel to produce the cationic amphiphilic microgels. This platform enables the rapid, automated, and in situ production of amphiphilic microgels, which do not match the core‐shell structure of conventionally prepared microgels but are instead based on random amphiphilic copolymers of DMAEMA and BuA between the hydrophobic cross‐links. The microgels are characterized in terms of their swelling and encapsulation abilities, which are found to be influenced by both the pH response and the hydrophobic content of the microgels. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 59–66 Abstract : Novel cationic amphiphilic microgels with hydrophobic and hydrophilic monomer units on the polymer chains were fabricated via an on‐chip polymerization methodology using a novel chip design.